Operation of a low-temperature differential heat engine for power generation via hybrid nanogenerators. (1st March 2021) - Zeeshan,; Panigrahi, Basanta Kumar; Ahmed, Rahate; Mehmood, Muhammad Uzair; Park, Jin Chul; Kim, Yeongmin; Chun, Wongee
Highlights: Nanogenerators were fabricated and operated using a Low Temperature Differential (LTD) heat engine. Contact sliding mode and vertical contact-separation mode were applied in 4 schemes. Two nanogenerators were operated simultaneously to exploit low-grade thermal energy. Nanogenerators along with an electromagnetic generator was also explored for power enhancement. Readily charged a capacitor to drive low power electronic appliances such as LEDs. Abstract: This work aims for the exploitation of low-grade thermal energy (<100 °C) in conjunction with the operation of nanogenerators run by a highly responsive low-temperature differential (LTD) heat engine. Two different types of nanogenerators were fabricated and tested in four different schemes: triboelectric in non-contact sliding mode (TENG), piezoelectric in contact-separation mode (PENG), triboelectric in contact-separation mode (TENG-2), and coupled triboelectric and piezoelectric in contact-separation mode (TENG-PENG). A series of tests were performed in generating power from the coupled action of triboelectric and piezoelectric nanogenerators with the operation of a LTD Stirling engine to harness low-grade thermal energy. This stands out as compared to previous studies from the perspective of operating two different types of nanogenerators in two different modes at the same time and the exploitation of low-grade thermal energy rather than the ambient mechanical energy, which is witnessed in most accomplishments in the relevant area. Running the triboelectric nanogenerator (non-contact sliding mode) with a small LTD heat engine (MM-7 Stirling engine) delivered a maximum output voltage of 35 V for a temperature difference of 73.2 °C. Meanwhile, the piezoelectric, triboelectric, and hybridized triboelectric-piezoelectric (contact-separation mode) nanogenerator produced output voltages of 4 V, 20.1 V, and 40 V, respectively. A maximum combined voltage of 74 V was also measured when the output of the triboelectric generator in noncontact sliding mode was combined with the hybrid (triboelectric-piezoelectric) nanogenerator operating in contact-separation mode. Operating the nanogenerators in conjunction with an electromagnetic generator (EMG) was also tested as appropriate, which clearly demonstrates the potential of their application in a hybrid manner if needed.